Beans in Honduras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Climate change and variability demands new varieties of beans. A Massive Participatory Assessment in Yojoa Lake in Honduras led by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) work together with local NGOs and farmers to make group observations and share their results with their neighbors